Condition survey on road work for pre & post 2 Apartment Service Block with 39 Floor Development Project / Izzah Kamilah Shaharuddin - Shaharuddin, Izzah Kamilah (2015)
K&P COVE CONSULTANCY SDN BHD has established itself on 29th June 2011 (formerly know n as Cove Consultancy) in conjunction with the expansion of various services to cater the current market demands of development industry services especially in Building Surveying and Building Management. The company comprises of professionals who have attained the standard required by Royal Institute of Surveyors Malaysia (RISM). All partners and employees in the organization are committed to conduct their operation with the highest level of professional integrity and ethic laid down by the Institute. Their core business activity is building survey (condition survey). This is a comprehensive visual inspection on existing building stocks. Building survey is carried out to all types of property, including dwelling, commercial, institutional, historical, industry and warehouse buildings.